Предмет: Алгебра, автор: romapetrosyan2019

Помогите срочно надо

Приложения:

Ответы

Автор ответа: Miroslava227
1

Ответ:

1.

f'(x) = 7 \times 7 {x}^{6}  + 13 \times 3 {x}^{2}  + 0 =  \\  = 49 {x}^{6}  + 39 {x}^{2}

2.

f'(x) =  \frac{1}{5}  + (4 {x}^{ - 3} )' + ( {x}^{ \frac{1}{2} } )' =  \\  =  \frac{1}{5}  + 4 \times ( - 3) {x}^{ - 4}  +  \frac{1}{2}  {x}^{ -  \frac{1}{2} }  =  \\  = 0.2 -  \frac{12}{ {x}^{4} }  +  \frac{1}{2 \sqrt{x} }

3.

f'(x) = (x(x + 2)) '= ( {x}^{2}  + 2x)' =  \\  = 2x + 2

4.

f'(x) = (x + 5)'( {x}^{2}  + 7) + ( {x}^{2}  + 7)'(x + 5) =  \\  =  {x}^{2}  + 7 + 2x(x + 5) =  \\  =  {x}^{2}  + 7 + 2 {x}^{2}  + 10x =  \\  = 3 {x}^{2}  + 10x + 7

5.

f'(x) =  \frac{( {x}^{2})'(2x + 1) - (2x + 1)' \times  {x}^{2}  }{ {(2x + 1)}^{2} }  =  \\  =  \frac{2x(2x + 1)   -   2 {x}^{2} }{ {(2x + 1)}^{2} }  =  \\  =  \frac{4 {x}^{2}  + 2x  - 2 {x}^{2} }{ {(2x + 1)}^{2} }  =  \frac{2 {x}^{2}  + 2x}{ {(2x + 1)}^{2} }

6.

f'(x) =  \frac{(x + 1)'(x - 2) - (x - 2)'(x + 1)}{ {(x - 2)}^{2} }  =  \\  =  \frac{x - 2 - (x + 1)}{ {(x - 2)}^{2} }  =  \frac{x - 2 - x - 1}{ {(x - 2)}^{2} }  =  \\  =   - \frac{3}{ {(x - 2)}^{2} }

Похожие вопросы